The correlation between perceived communication quality and customer satisfaction at Bhayangkara Hospital Emergency Department, Indonesia - Alita Dewi Percunda; Djazuli Chalidyanto (AOSIS, 2019)
Overcrowding at emergency department with domination of non-emergency patient based on triage process could lead to the decrease of communication quality from the care giver. An approach through communication media at hospital should be optimized to fulfill the information needs from the customer. This study aimed to identify the correlation between the communication quality and the customer satisfaction can give us a better understanding to improve our service at emergency department. A questionnaire to measure perceived communication quality of care giver (consists of communicator and media aspects) and customer satisfaction was given to patient or his/her guardian at emergency department. The sample size of 93 had been validated from 100 questionnaires collected. The regression test result is significant for both communicator aspects (sig 0.000) and information media (sig 0.011) with p<0.05. The perceived communication quality both communicator and media aspect is correlated with customer satisfaction. Thus, understanding and improvement in those factors are important to increase customer satisfaction especially at emergency department where situations are often busy and care givers tend to underestimate the importance of communication.